2022
DOI: 10.1097/aln.0000000000004254
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of High-flow Nasal Cannula and Upper-body Elevation for Postoperative Sleep-disordered Breathing: Randomized Crossover Trial

Abstract: Background Low acceptance rate of continuous positive airway pressure therapy in postoperative patients with untreated obstructive sleep apnea (OSA) indicates the necessity for development of an alternative postoperative airway management strategy. We considered whether the combination of high-flow nasal cannula and upper body elevation could improve postoperative OSA. Methods This non-blinded randomized crossover study perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…2,3 Surprisingly, this was not observed here. Conversely, oxygenation in the 30-degree head-of-bed elevation group was inferior to that in the supine position (table 2 1 ). Curiously, although the combination of high-flow nasal oxygen and 30-degree head-of-bed elevation showed additive or even synergistic effects, neither alone showed much impact on the apnea-hypopnea index.…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…2,3 Surprisingly, this was not observed here. Conversely, oxygenation in the 30-degree head-of-bed elevation group was inferior to that in the supine position (table 2 1 ). Curiously, although the combination of high-flow nasal oxygen and 30-degree head-of-bed elevation showed additive or even synergistic effects, neither alone showed much impact on the apnea-hypopnea index.…”
Section: To the Editormentioning
confidence: 95%
“…The analysis, by Sakaguchi et al ., of the role of high-flow nasal oxygen administered postoperatively in those diagnosed with obstructive sleep apnea (OSA) in lieu of conventional continuous positive airway pressure therapy is interesting. 1 We would welcome further commentary from the authors on a few points, however.…”
Section: To the Editormentioning
confidence: 99%
“…We thank Roy et al 1 for their relevant comments on our article. 2 As Roy et al correctly pointed out, head-of-bed elevation by 30 degrees did not significantly improve oxygenation variables such as mean nadir oxygen saturation measured by pulse oximetry (Sp o 2 ), lowest Sp o 2 , and percent time Sp o 2 < 90% in our study although, Souza’s previous study demonstrated improvement of both apnea hypopnea index (15.7 to 10.7 events/h) and lowest Sp o 2 (83.5 to 87%) in symptomatic obstructive sleep apnea (OSA) patients with only 7.5-degree head-of-bed elevation. 3 It would be easy to comment that different patient populations and study design are the cause of the difference.…”
Section: In Replymentioning
confidence: 99%
“…These issues provide the rationale for a study reported in this issue of Anesthesiology that considers an alternative approach to continuous positive airway pressure therapy to treat sleep disordered breathing postoperatively. 5…”
mentioning
confidence: 99%
“…address this knowledge gap adroitly, and in so doing help draw attention both to these therapeutic options and, more generally, to the case for non–continuous positive airway pressure alternatives for postoperative OSA management. 5…”
mentioning
confidence: 99%